2011
DOI: 10.1021/cn200094j
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Visualization of Ultrastructural Features of Artificial Synapses via Cryo-EM

Abstract: ABSTRACT:The ultrastructural details of presynapses formed between artificial substrates of submicrometer silica beads and hippocampal neurons are visualized via cryoelectron microscopy (cryo-EM). The silica beads are derivatized by poly-D-lysine or lipid bilayers. Molecular features known to exist at presynapses are clearly present at these artificial synapses, as visualized by cryo-EM. Key synaptic features such as the membrane contact area at synaptic junctions, the presynaptic bouton containing presynaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…76 We and others have demonstrated that interactions with artificial cues can also alter cell growth patterns similarly to the interactions of neurons with other neurons. 19,26,27 In this study, we were able to compare distinct morphological parameters together with wide genetic profiles of neurons without any contact, interconnected, or in contact with nanostructures. In a previous study, we emphasized the critical role of physical interactions in neuronal growth and guidance on similar nanostructures.…”
Section: Nano Lettersmentioning
confidence: 99%
See 2 more Smart Citations
“…76 We and others have demonstrated that interactions with artificial cues can also alter cell growth patterns similarly to the interactions of neurons with other neurons. 19,26,27 In this study, we were able to compare distinct morphological parameters together with wide genetic profiles of neurons without any contact, interconnected, or in contact with nanostructures. In a previous study, we emphasized the critical role of physical interactions in neuronal growth and guidance on similar nanostructures.…”
Section: Nano Lettersmentioning
confidence: 99%
“…26 Characteristic features of presynaptic structural elements, such as presynaptic vesicles and microtubular structures, were visualized at these artificial synapse sites. 27 These effects of neuron−substrate interactions, which are reminiscent of those observed after neuron−neuron interaction, raise the question, "What are the functional interactions fundamental to the neuronal network?". To answer this question, we grew identical neuronal populations in three distinct connectivity states: isolated neurons, interconnected neurons, and isolated neurons, in contact with artificial nanotopographical cues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of complex systems with a synchronized sample analysis and modification is expected within the modern tendency to the combination of the systems biology as an analytical approach with the reverse constructive approachsynthetic biology or the design of some arbitrary artificial biological / biomimetic structures. Thus, the analysis of natural biological structures (e.g., flagella and ciliary structures of the protozoa [17]) and semi-synthetic objects (those synthesized artificially from the biochemical components), such as 3D protein crystals for crystallographic studies [82], lays the foundation for cryo-electron 3D-morphological analysis of synthetic DNAorigami [6] and even more complex hybrid artificial structures, such as an artificial synaps [43]. Despite the fact that in some cases due to the planar 2D structure of the sample a less dimensional analysis may be sufficient enough to obtain the morphological data (cryo-electron microscopy instead of cryo-tomography) [58,126], the increase in the analysis dimension generally leads to the enlargement of the data amount, and hence, improves its heuristic value, providing new opportunities for the quantitative analysis [113].…”
Section: From Systems To Synthetic Biology Through Cryo-electromentioning
confidence: 99%
“…To date, numerous synthetic compounds of either biochemical or nonbiological nature are used as imaging agents in cryo-electron microscopy [13,87], but even in pure biological and biomimetic research the main aim of the combined structural and chemical analysis is to perform non-destructive testing, i.e. ultrastructure visualization without any chemical modifiers and specific markers [43].…”
Section: The Analyte Distribution Mapping and The Descriptor Imaging ...mentioning
confidence: 99%